Peranan gaji, penyeliaan, peluang kenaikan pangkat, pengiktirafan dan persekitaran kerja terhadap kepuasan kerja staf Felcra Berhad - Aidatul Sima, Mohd Sharif (2023)
Issues on job satisfaction is significant to the engagement, aspiration and commitment among employees. Among the factors that contribute to the success of organization is when the employees have positive work aspiration such as having career goals, have high enthusiasm at the workplace, having positive attitudes and feelings towards their own profession. If employees have high work aspiration towards their organization, it is indirectly will increse employees’ commitment towards the organization. Therefore, this study is conducted to capture factors that might influence job satisfaction among employees in agriculture sector. The study examines the direct relationship between salary, supervision, promotion opportunity, recognition, work environment and job satisfaction. A total of 243 questionnaire were distributed online through Google form. A total of 239 questionnaire were recieved, yielding a response rate of 98.35%. In this study, hypotheses for direct effect were tested using multiple regression analyses. Results showed that only supervision and work environment were found significantly positively related to job satisfaction. The findings indicate that job satisfaction can be increased by improving on quality of supervision and providing condusive working environment and good support system.